PENGARUH PENDEKATAN SCIENCE TECHNOLOGY SOCIETY (STM) TERHADAP HASIL BELAJAR SISWA PADA MATERI EKOSISTEM DI SMP IT MA’ARIF AL GHOZALI - Indra Drajat Sopwan (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2022)
Research on The Effect of the STM Approach Against Student Learning Outcomes on the Ecosystem in Class two of Ma'arif Junior High School 2020/2021 Academic Year which is the main problem of the is study: is there an effect of the STM approach on student learning outcomes and how much influence it has. The purpose of this study is to determine whether there is an influence of the STM approach to student learning outcomes. In accordance with these objectives, the research method in processing data is to use a quantitative approach through t test. The sample in this study were 91 students consisting of two classes, one control class of 46 people and one experimental class of 45 people. Data collection tools used in this study are objective test. Based on the analysis of data obtained an average for the control group (X = 5.326). While the average for the experimental group (X = 6.933) and the distribution normality test results showed that both of them were not normally distributed, then subsequently using non-parametric statistics, namely the Wilcoxon test so that the results obtained W hit < W table means that there are significant differences between the dick group with the experimental group and the degree of influence of E = 55.65%. Thus there is a significant difference in improving learning outcomes between those who use the STM approach, and those who do not use STM. This STM approach will be better understood by students, where students are very involved in the implementation of teaching and learning activities and the teacher is only a facilitator